Human rights education in patient care - Joanna N. Erdman (Frontiers Media S.A., 2017)
Abstract This article explores how human rights education in the health professions can build knowledge, change culture, and empower advocacy. Through a study of educational initiatives in the field, the article analyzes different methods by which health professionals come to see the relevance of human rights norms for their work, to habituate these norms in everyday practice, and to espouse these norms in advocacy for social justice. The article seeks to show the transformative potential of education for human rights in patient care.